Allosteric nanobodies uncover a role of hippocampal mGlu2 receptor homodimers in contextual fear consolidation. Issue 1 (December 2017) - Scholler, Pauline; Nevoltris, Damien; de Bundel, Dimitri; Bossi, Simon; Moreno-Delgado, David; Rovira, Xavier; Møller, Thor; El Moustaine, Driss; Mathieu, Michaël; Blanc, Emilie; McLean, Heather; Dupuis, Elodie; et al.
Abstract Antibodies have enormous therapeutic and biotechnology potential. G protein-coupled receptors (GPCRs), the main targets in drug development, are of major interest in antibody development programs. Metabotropic glutamate receptors are dimeric GPCRs that can control synaptic activity in a multitude of ways. Here we identify llama nanobodies that specifically recognize mGlu2 receptors, among the eight subtypes of mGluR subunits. Among these nanobodies, DN10 and 13 are positive allosteric modulators (PAM) on homodimeric mGlu2, while DN10 displays also a significant partial agonist activity. DN10 and DN13 have no effect on mGlu2-3 and mGlu2-4 heterodimers. These PAMs enhance the inhibitory action of the orthosteric mGlu2/mGlu3 agonist, DCG-IV, at mossy fiber terminals in the CA3 region of hippocampal slices. DN13 also impairs contextual fear memory when injected in the CA3 region of hippocampal region. These data highlight the potential of developing antibodies with allosteric actions on GPCRs to better define their roles in vivo. G protein-coupled receptors are considered promising therapeutic targets. Here, the authors have identified nanobodies, or single-domain llama antibodies, that specifically enhance agonist-induced activity of a type of G protein-coupled receptor, the mGlu2 receptor.